On the Gauss sums and generalized Bernoulli numbers - Gao, J.; Liu, H. (Український математичний журнал, 2012)
Using the properties of primitive characters, Gauss sums, and the Ramanujan sum, we study two hybrid mean values of Gauss sums and generalized Bernoulli numbers and give two asymptotic formulas. Iз використанням примiтивних характерiв, сум Гаусса та суми Рамануджана вивчено два гiбридних середнiх значення сум Гаусса й узагальнених чисел Бернуллi та отримано двi асимптотичнi формули.